使用接龙游戏提高KOPERASI 高中二年级学生对词汇的掌握分析 - Achmad Arief Santosa; Lily Thamrin; Suhardi Suhardi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThe game teaching method is mainly for students to play in middle school and play in school. The Author uses the Solitaire game teaching method to conduct research, the purpose is to understand whether students can improve their ability to master new words in the teaching of Solitaire game. The author conducted an experiment in the second grade science class of Koperasi high school. After the teaching experiment, the Author obtained the result that the use of Solitaire game teaching can improve students' ability to master new words and also improve students' test scores. The student's post-test score is higher than the pre-test score. The average score of the student's pre-test is 55.2 points. After using the Solitaire game teaching method, the average score of the student test is 82 points. The Author uses the school’s passing score as the standard score, which is 70 points. According to the school’s standard score, which is 70 points. According to the school’s standard score, after using the Solitaire game teaching method, the student’s passing rate of the post-test was 88%. This means that the use of solitaire game teaching in the teaching process can help improve students' mastery. 'Keywords: Vocabulary, Solitaire Game, Teaching Method